Structure of Broad-Scale Management in the Vernadsky Station Area - Fedchuk, A. (Український антарктичний журнал, 2009)
The article is devoted to actual issues on methodological provisions for Antarctic activity. Geographical distribution and further diversification of human activities in this region became an environmental threat that needs more comprehensive approach for management in Antarctic in whole and specifically in the region of Ukrainian scientific interests. Стаття присвячена актуальним питанням науково-методичного забезпечення антарктичної діяльності, географічне поширення та подальша диверсифікація якої набувають нових загрозливих масштабів як в Антарктиці в цілому, так і в зоні відповідальності станції Академік Вернадський зокрема. Статья посвящена актуальным вопросам научно-методического обеспечения антарктической деятельности, географическое распространение и дальнейшая диверсификация которой приобретают новые угрожающие масштабы как в Антарктике в целом, так и в районе станции Академик Вернадский в частности. Проанализирована функциональная структура основных типов подохранных территорий Антарктики, показаны причины их высокой концентрации вдоль северо-западной оконечности